The Influence of Conflict Behavior and Conflict Management on Employee Performance at PT. Pos Indonesia Ambon Branch - Paulus L Wairisal (CV Putra Publisher, 2022)
Conflict is often caused by systems and structures. An inappropriate system will easily lead to conflict and differences in positions in the structure will also lead to conflict. Differences in team members in terms of education, organization, ability, cultural background, can produce different perspectives in completing tasks which are antecedent factors of conflict. The purpose of this study is to analyze and explain the effect of conflict behavior on employee performance, the effect of conflict management on performance and the effect of conflict management on strengthening conflict behavior on employee performance. The unit of analysis in this study were employees of PT. Pos Indonesia Ambon Branch, totaling 108 people. The results showed that 1) the conflicting behavior of the relationship indicators with items of feeling disliked, the presence of tension at work, the presence of personal barriers and indicators of task conflict with items rejecting other people's ideas, refusing other people's ways of working, looking down on other people had a significant effect on employee performance, 2) management with item collaboration conflict indicators actively looking for joint solutions, offering solutions for employees, item confrontation indicators ignoring the ideas offered, making decisions unilaterally, item accommodation indicators paying attention to the ideas offered, accepting every idea that is offered. offered, responding to every complaint, affecting employee performance, and 3) conflict management behavior collaboration, confrontation, accommodation has an effect on strengthening relationship conflicts and task conflicts on employee performance